Games in EFL classrooms: developing oral skills in English and promoting multiple intelligences. (2022)
The purpose of this research paper is to mention some thoughts that teachers have about the use of the game as a didactic teaching tool for English. That said, the document seeks to provide a solution to teachers where they are shown that the game is effective in oral production in teaching English. Considering these elements, this paper is a qualitative research based on narrative analysis methods that have taken place in El Bagre, Antioquia. First, mention the data gathered obtained from an interview about the different conceptions that teachers have about games from their own experiences. Second, a focus group was developed to apply games as a didactic-pedagogical strategy in teaching practice. The result showed that games have different educational purposes in teaching-learning a second language. However, the finding suggests the inadequate use that teachers give to games as a strategy.In light of these aspects, for future research it is recommended to continue promoting the implementation of games in classrooms and the curriculum, in order to keep transforming the educational reality.